KEEFEKTIFAN MODEL PEMBELAJARAN KONTEKSTUAL DENGAN PENDEKATAN OPEN ENDED DALAM PEMECAHAN MASALAH - Joko Sulianto (Jurnal Ilmu Pendidikan, 2012)
Abstract: The Effect of Open-ended-based Contextual Learning on the Problem-solving Ability of the Students. The study tries to describe the effect of open-ended-based contextual learning on the ability of the first grade of junior high school students in problem solving. The study is based on an experiment involving two different groups. One group was taught by using open-ended-based contextual learning model and the other was taught using an expository learning model. The result of the experiment shows that students' ability in problem solving taught using open-ended-based contextual learning model is better that ability of the students taught using expository learning model.